2013
DOI: 10.4236/crcm.2013.23054
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Rhabdomyolysis in the setting of acute human immunodeficiency virus infection

Abstract: Acute HIV infection (AHI) is often marked by nonspecific and vague complaints, which make detection difficult. An 18-year-old man presented with one week history of subjective fevers with chills, nonproductive cough and generalized body aches. He was found to have rhabdomyolysis due to AHI. This report adds the most thoroughly investigated case of AHI-associated rhabdomyolysis to date, having ruled out erlichia, legionella, parainfluenza, adenovirus, enterovirus, metapneumovirus, RSV and DILS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Our review of the literature found most of the reported cases being in immunocompromised patients with HIV infection [10] [11] [12], or allogeneic stem cell transplant recipient [11] [13]. To the best of our knowledge, our patient is the third case of SMX-TMP-induced rhabdomyolysis in an immunocompetent patient, and the second of the immunocompetent patient to have multiple attributing factors [14] [15].…”
Section: Introductionmentioning
confidence: 89%
“…Our review of the literature found most of the reported cases being in immunocompromised patients with HIV infection [10] [11] [12], or allogeneic stem cell transplant recipient [11] [13]. To the best of our knowledge, our patient is the third case of SMX-TMP-induced rhabdomyolysis in an immunocompetent patient, and the second of the immunocompetent patient to have multiple attributing factors [14] [15].…”
Section: Introductionmentioning
confidence: 89%